The effects of Greenfield FDI and cross-border M&As on total factor productivity - Ayesha Ashraf; Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2014)
We examine and compare the effects of greenfield FDI and cross-border mergers and acquisitions (M&As) on total factor productivity (TFP) in developed and developing host countries of FDI. Using panel data for up to 123 countries over the period from 2003 to 2011, we find that greenfield FDI has no statistically significant effect on TFP while M&As have a positive effect on TFP in the total sample. Greenfield FDI and M&As both appear to be ineffective in increasing TFP in the sub-sample of developing countries. In contrast, M&As have a strong and positive effect on TFP in the sub-sample of developed countries.
Keywords: F21; F23; O47; 330; greenfield FDI; cross-border mergers and acquisitions; total factor productivity